Makna dan Penerapan Uang Pisah pada Pemutusan Hubungan Kerja dalam Hukum Ketenagakerjaan Indonesia - Ari Hernawan (Fakultas Hukum Universitas Islam Indonesia, 2023)
The Employment Law, the Job Creation Law and their derivatives only provide separation pay as an obligation of the employer which must be fulfilled to the employee when terminating their employment relationship due to certain reasons, while leaving the amount to be regulated in the separate work agreement, the company regulations or the collective work agreement. The absence of authentic interpretation and provisions regarding the amount of separation pay in employment regulations in Indonesia raises problems in both the meaning and the application of the law. The questions raised in this research are whether the court decision that applies the amount of severance pay the same as the amount of reward for the fulfilled term of office is correct, and is the meaning behind setting the amount of separation pay determined in the work agreement, the company regulations, or the collective work agreement. This research aims to identify and analyze the aforementioned problems. The research method used is normative and analytical descriptive which relies on secondary data as the source. The results of the research display that, in cases where it is not regulated, the judge ultimately determines the amount of separation pay to be the same as the calculation of the gratuity for long service. This is not entirely correct because the reward for a long period of service is intended as a gratuity for years of service that has been dedicated to the company so that rational considerations are the basis for the calculation and separation money is intended more as a bond of love so that the moral dimension is stronger.Keywords: Employment Law, Implementation, Meaning, Severance Pay, Work Termination AbstrakUndang-Undang Ketenagakerjaan dan Undang-Undang Cipta Kerja beserta turunannya hanya menyatakan uang pisah sebagai kewajiban pengusaha yang harus diberikan kepada pekerja dalam pemutusan hubungan kerja dengan alasan tertentu dan menyerahkan besarannya untuk diatur dalam perjanjian kerja, peraturan perusahaan, atau perjanjian kerja bersama. Tidak adanya penafsiran otentik dan ketentuan mengenai besaran uang pisah dalam peraturan ketenagakerjaan di Indonesia membawa permasalahan dalam makna dan penerapan hukumnya. Pertanyaan yang diangkat dalam penelitian ini ialah apakah putusan pengadilan yang menerapkan besaran uang pisah sama dengan besaran uang penghargaan masa kerja sudah tepat, dan apakah makna dibalik pengaturan besaran uang pisah ditentukan dalam perjanjian kerja, peraturan perusahaan, atau perjanjian kerja bersama. Adapun tujuan dari penelitian ini ialah untuk mengetahui dan menganalisis permasalahan yang diangkat sebagaimana disebutkan. Metode penelitian yang digunakan ialah normatif dan bersifat deskriptif analitis yang mengandalkan data sekunder sebagai sumber data. Hasil penelitian menunjukkan, dalam hal tidak diatur, hakim pada akhirnya menentukan besaran uang pisah sama dengan perhitungan uang penghargaan masa kerja. Hal tersebut tidak sepenuhnya tepat karena uang penghargaan masa kerja dimaksudkan sebagai penghargaan atas masa kerja yang sudah diabdikan kepada perusahaan sehingga pertimbangan rasional menjadi dasar perhitungannya dan uang pisah lebih dimaksudkan sebagai tali kasih sehingga dimensi moral lebih kental.Kata Kunci: Hukum Ketenagakerjaan, Makna, Pemutusan Hubungan Kerja, Penerapan, Uang Pisah